Capturability of Impact-Angle Control Composite Guidance Law Considering Field-of-View Limit - Lee, Seokwon; Kim, Youdan (IEEE transactions on aerospace and electronic systems, 2020)
A capture region of the composite guidance law is analyzed for a missile equipped with a strapdown seeker. The composite guidance law consists of a deviated pure pursuit guidance law and a pure proportional navigation guidance law to perform impact-angle control. The range of the field-of-view limit restricts the performance of the guidance law, which reduces the capture region. Based on the characteristics of the guidance law, the range of the achievable impact angle is investigated by considering the collision condition and the field-of-view limit. It is shown that the capture region is represented in terms of the relative initial position and terminal flight-path angle. Numerical simulations are performed to investigate the properties of the proposed capture region of the composite guidance law.